Preliminary Functional Outcome Following Robotic Intracorporeal Orthotopic Ileal Neobladder with Integrated Pelvic Fascial Structure-Sparing in Males with Bladder Cancer - Xu, Xin; Liang, Zhen; Feng, Yanfei; Qi, Honggang; Wang, Shuo; Xia, Dan; Wang, Ping (Urology Journal, 2025)
Purpose: To describe our integrated pelvic fascial structure-sparing (IPFSS) technique for robotic-assisted radical cystectomy (RARC) with intracorporeal orthotopic neobladder (ONB) reconstruction and to evaluate its impact on urinary continence and sexual function in male patients. Methods: This retrospective observational study was conducted at a single high-volume center. Male bladder cancer patients who underwent IPFSS RARC with ONB were included. Demographic, clinical, and pathological data were collected. Functional outcomes were evaluated and compared with a cohort of patients who underwent conventional non–nerve-sparing RARC. Results: Thirty-six patients were included in the IPFSS group and 42 in the conventional group. RARC with intracorporeal urinary diversion was successfully completed in all patients without open conversion. The mean total operative time was 387.9 minutes in the IPFSS group and 392.0 minutes in the conventional group (p = 0.465). At 3 months post-surgery, 30 patients (83%) in the IPFSS group achieved daytime continence (0–1 pads), compared to 14 patients (33%) in the conventional group. By 6 months, daytime continence increased to 35 patients (97%) in the IPFSS group, while 28 patients (67%) in the conventional group achieved similar results. At 6 months, 30 patients (83%) in the IPFSS group reported full potency with or without phosphodiesterase type 5 (PDE5) inhibitors, compared to only 3 patients (7%) in the conventional group. Conclusion: We present a feasible surgical technique for RARC that involves holistic preservation of the pelvic fascial architecture. This approach is associated with a rapid recovery of daytime continence and sexual function in male patients.